Anomalies in the bulk and surface electronic properties of SnS: effects of native defects. Issue 14 (10th March 2022) - Dahule, Rohit; Singh, Chetan C.; Hongo, Kenta; Maezono, Ryo; Panda, Emila
Abstract : A combinatorial approach of experiment and theory was used to investigate the defect induced bulk and surface electrical properties of SnS. Abstract : SnS is a promising photovoltaic absorber material because of its low cost and lower toxicity and is usually present in a heterostructure. Understanding the bulk and the surface electrical properties would help in the understanding of the transport behavior and hence would be extremely useful in fabricating high performance devices. In this regard, here a combinatorial approach of experiment and theory was used to understand the anomalies in the bulk and the surface electrical properties of SnS. Experimentally, single phase polycrystalline SnS films are fabricated by RF magnetron sputtering and characterized for their detailed microstructure, and optical, bulk and surface electrical properties. The observed anomalies in their bulk and surface electrical properties are then interpreted through first-principles density functional theory (DFT) calculations of the bulk and the surface electronic structures. DFT calculations on various native surface defects provided further insights into the experimentally observed semi-metallic behavior using scanning tunnelling spectroscopy.